Preterm prelabour rupture of membranes with bicornuate uterus- A case report - Samra Mobeen; Nabiha Iqbal; Fatima Ismail; Sikandar, Mirza Zeeshan; Sharoona Fatima (Journal of the Pakistan Medical Association, 2026)
A 29-year-old primiparous woman with a diagnosed bicornuate unicolis uterus presented at 30 weeks of gestation to the emergency triage due to preterm prelabour rupture of membranes PPROM. An emergency caesarean section was opted as the mode of delivery. Laboratory analyses showed the presence of an infectious agent, and ultrasonography confirmed the bicornuate uterus. A caesarean section was done followed by delivery of baby girl with good APGAR score and a weight of 1.7kg. The neonate gained 500 g during 7 days of hospitalization and was discharged. This case displays that this anomaly requires advanced management when present during pregnancy and underscores the importance of multidisciplinary care in achieving optimal outcomes. Key Words: Preterm prelabour rupture of membranes, bicornuate uterues, unicollis.